2000
DOI: 10.1002/cjce.5450780404
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the aeration of small bitumen droplets

Abstract: n the processing of Athabasca oil sands, bitumen' is recovered from the slurried ore via water-based flotation methods, as first developed I by Clark and Pasternack (1932). As the densities of bitumen and water are virtually identical at processing temperatures (Liu, 1989; Pandit et al., 1995;Basu et al., 1996, Shaw et al., 1996, it is essential that a density difference between the two phases be created through aeration of the liberated bitumen drops. In the subsequent flotation step, the aerated bitumen/wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…Using a micromechanical device, Moran et al [11] observed that bitumen did not make contact with an air bubble surface when kaolinite was present in the solution. The tests of Moran et al [11] were conducted in simulated process water that contained many different electrolytes, including 0.3 mmol/L CaCl 2 and 0.3 mmol/L MgCl 2 .…”
Section: Previous Studies On Bitumen-mineral Liberationmentioning
confidence: 98%
“…Using a micromechanical device, Moran et al [11] observed that bitumen did not make contact with an air bubble surface when kaolinite was present in the solution. The tests of Moran et al [11] were conducted in simulated process water that contained many different electrolytes, including 0.3 mmol/L CaCl 2 and 0.3 mmol/L MgCl 2 .…”
Section: Previous Studies On Bitumen-mineral Liberationmentioning
confidence: 98%
“…The efficiency of their attachment would therefore depend on the hydrodynamic and water chemistry environment of the system. In terms of the effect of bitumen droplet size on bitumen-bubble attachment, a recent study using a micropipette technique by Moran et al (2000b) and Yeung and Moran (2000b) indicated that smaller bitumen droplets in the micron size range were much more difficult to attach to an air bubble than the droplets in the millimeter size range. Although a positive spreading coefficient exists in bitumen-air bubble systems, the aeration of bitumen droplets appears not always guaranteed.…”
Section: Bitumen and Bubble Sizementioning
confidence: 99%
“…The interfacial tensions between LM-Ath-C7 asphaltenes dissolved in toluene and distilled water were measured with a micropipette apparatus [57] using the maximum bubble pressure method [58].…”
Section: Interfacial/surface Tension Measurementsmentioning
confidence: 99%